Representações sociais de professores e alunos universitários acerca do ensino remoto emergencial - Pinto, Izabel Cavalcanti Barros Lamenha (2023)
Emergency remote teaching is a teaching modality that was implemented by educational institutions worldwide, in response to the Covid-19 pandemic, to continue teaching and learning activities. At this juncture, we sought the theoretical contribution of the Theory of Social Representations - TRS, to explain how teachers and university students learned knowledge about the social environment, as well as the impacts that affected the way people thought, acted, and related during remote teaching. The aim of the study was to learn about the meanings and senses of university teachers and students about emergency remote teaching in the context of Covid-19. The thesis was divided into two parts one theoretical and the other composed of empirical studies. In the first part is the introduction, followed by two theoretical chapters. The first chapter is titled, contextualization of the object of study and the second is focused on the theoretical contribution of social representations. The second part contains three empirical studies on the theme. The first study, entitled, what do college professors and students think after remote teaching: a psychosociological analysis, aimed at knowing the social representations elaborated by the same participants, however, the data analysis occurred in the Alceste software, by the Descending Hierarchical Classification - HDC technique. The results pointed out that teachers and students developed adaptation strategies, anchored, in the psychosocial sphere, constructing the objectifications in the terms necessity and maintenance of teaching. As for the elements, future and hybrid, the anchoring occurred in a macro-structural sphere. Students perceived remote classes in a technological and ambivalent sphere, objectifying both for usability difficulties and digital tools and for the novelty of the modality. Study two, entitled, Emergency remote teaching: social representations for university teachers and students in the Covid-19 pandemic, aimed to apprehend the social representations elaborated by these participants about emergency remote teaching. The study sample was composed of 147 teachers and 130 college students who answered the Free Association of Words Technique - TALP, by the inductive stimuli, remote teaching and hybrid teaching, besides the sociodemographic questionnaire. The SPSS software (version 21.0) and the Correspondence Factor Analysis by means of Tri-Deux-Mots were used to analyze the data. The results for remote teaching pointed out that teachers, evaluative-valuative manifestations emerged according to the emergent character of the phenomenon and the affectivebehavioral dimension, by facing the new. In the hybrid stimulus, besides the previous anchorages, manifestations also emerged in the sociocultural sphere, related to technological and methodological innovation. The students also anchored the remote teaching in an evaluative-valuative and affective-behavioral way, as well as in the hybrid teaching brought repercussions to the teachinglearning process. Study three, entitled Academic satisfaction of college students during emergency remote teaching, aimed to measure students' satisfaction during their experience with remote teaching, by means of the Scale of Academic Satisfaction of College Students - ESAU. A total of 208 college students from private higher education institutions in the state of Paraíba - PB were studied. The results revealed a balance between the general scores of satisfactions and dissatisfaction among the students. The lowest levels of dissatisfaction were related to the perceptions of the pedagogical environment, affective perceptions, and self-esteem. The highest levels were identified in perceptions of the physical environment. It is recommended that educational institutions consider the unsatisfactory incidents to improve the educational process when adopting online or hybrid methodologies in their programs. Moreover, remote teaching was an emergency and temporary strategy, and the need arose for didacticmethodological organization to overcome the difficulties faced throughout the process, when elements emerge that are close and/or concomitantly present in both participants, such as challenge, difficulty, adaptation, and need. Moreover, it is necessary to strengthen the support to teachers and students, especially on the psychosocial and technological issues, so that they can increase the gains obtained throughout the process, as revealed by the elements important, flexibility, practical, and new. Moreover, it is believed that the results of this thesis can also contribute to the implementation of the hybrid modality, indicated in all studies as a positive experience by teachers and students, and emerges as an innovation to be widely consolidated in the future in higher education institutions as a teaching offer, ensuring more curricular flexibility and learning opportunities differentiated using technological resources and tools.